2020
DOI: 10.1021/acs.cgd.0c00857
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Features, and Hydrogen Adsorption Properties of Three New Flexible Sulfur-Containing Metal–Organic Frameworks

Abstract: Three novel flexible sulfur-containing MOF materials named Co-URJC-5, Cu-URJC-6 and Zn-URJC-7, based on the 5,5′-thiodiisophthalic acid linker have been synthesized through solvothermal methods and characterized by different physicochemical techniques. Hydrogen adsorption analysis at room temperature reveals that these compounds display a gate-opening type adsorption mechanism at low pressures, attributed to the flexible nature of the H4TBTC ligand. This behavior is even more noticeable for Cu-URJC-6, since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Recently, we have reported the interesting H 2 uptake gate‐opening behavior of a Co(II)‐based MOF as known Co‐URJC‐5 (URJC=Universidad Rey Juan Carlos), which is formed by 5–5'‐thiodiisophthalic acid as a ligand and a saturated single octahedral cobalt(II) cluster with two pyridine molecules in axial positions (Figure S1) [17] . Due to the flexible performance and the lack of OMS we decided to investigate the SO 2 adsorption properties of this material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have reported the interesting H 2 uptake gate‐opening behavior of a Co(II)‐based MOF as known Co‐URJC‐5 (URJC=Universidad Rey Juan Carlos), which is formed by 5–5'‐thiodiisophthalic acid as a ligand and a saturated single octahedral cobalt(II) cluster with two pyridine molecules in axial positions (Figure S1) [17] . Due to the flexible performance and the lack of OMS we decided to investigate the SO 2 adsorption properties of this material.…”
Section: Introductionmentioning
confidence: 99%
“…Co‐URJC‐5 was obtained via a solvothermal reaction of Co(NO 3 ) 2 ⋅ 6H 2 O with 5–5'‐thiodiisophthalic acid (H 4 TBTC: Scheme 1) according to a reported procedure [17] . A pink crystalline solid was obtained and characterized by X‐ray diffraction and N 2 adsorption which afforded a BET surface area of 233 m 2 g −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen adsorption analysis of three flexible sulfur-containing MOF materials named M-URJC-n (M = Co, Cu, Zn) based on the 5,5′-thiodiisophthalic acid linker (H 4 TBTC) showed that these compounds display a gate-opening type adsorption mechanism at low pressures, attributed to the flexible nature of the ligand [ 113 ]. The hydrogen adsorption capacities of the compounds were not high, with levels of 2.81, 2.21, and 1.99 wt%, for Co–, Cu–, and Zn modification, respectively, at 77 K and up to 18 bar, and 0.12, 0.14, and 0.13 wt%, at 298 K and 170 bar, due to the presence of flexible ligands.…”
Section: Current Approaches To Increasing Hydrogen Adsorption In Mofsmentioning
confidence: 99%
“…These compounds showed an interesting gate-opening type adsorption mechanism. Considering the flexibility and the dynamic nature of the new structures, these compounds are candidates for applications such as hydrogen selective adsorption and gas separation processes, including hydrogen purification in precombustion mixtures of H 2 /CO 2 [ 113 ].…”
Section: Current Approaches To Increasing Hydrogen Adsorption In Mofsmentioning
confidence: 99%